2022
DOI: 10.1371/journal.pone.0268123
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of patients with low back pain attending a Canadian emergency department: Why they came and what happened?

Abstract: Low back pain is a common presentation to emergency departments, but the reasons why people choose to attend the emergency department have not been explored. We aimed to fill this gap with this study to understand why persons with low back pain choose to attend the emergency department. Between July 4, 2017 and October 1, 2018, consecutive patients with a complaint of low back pain presenting to the University of Alberta Hospital emergency department were screened. Those enrolled completed a 13-item questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…We analysed the proportion of low back pain admissions from ED from 3 government reports25 28 43 and 20 peer-reviewed studies14 16–19 40 42–56 (table 1). Seven studies were from healthcare systems with predominantly private funding, 16 with predominantly public funding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed the proportion of low back pain admissions from ED from 3 government reports25 28 43 and 20 peer-reviewed studies14 16–19 40 42–56 (table 1). Seven studies were from healthcare systems with predominantly private funding, 16 with predominantly public funding.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies reported a median age ranging from 43 to 69 years for people with back pain, who presented to the ED and were admitted as inpatients. Age stratified admission rates would likely reflect higher admission rates in older people presenting to hospital, given the higher rates of ED low back pain presentations for those aged >75 years,72 and the higher low back pain admission rates seen for cohorts of greater median age 17 47…”
Section: Discussionmentioning
confidence: 99%
“…All studies undertook audits of hospital records and databases except the cross-sectional study that used interviews and self-reported outcomes [ 28 ]. The International Classification of Diseases (ICD) or the Systematized Nomenclature of Medicine—Clinical Terms (SNOMED-CT) primary discharge diagnoses for non-specific LBP conditions or sciatica were used for the inclusion criteria in all but three studies, where participants self-reported their LBP [ 28 , 44 , 51 ]. Data capture period or participant recruitment ranged from six months to 45 years, and follow-up of participants ranged between 180 days and 34 years from baseline.…”
Section: Resultsmentioning
confidence: 99%
“…One cohort study with low risk of bias set in emergency departments found people 65 years of age and older had greater odds of hospitalisation compared to people of younger age (OR 3.0, 95% CI 2.59–3.59) [ 34 ]; and in a similar study also set in emergency departments, the odds were even greater in people over 85 years of age (OR 5.45 95% CI 5.34 5.57) [ 27 ]. Three other studies with moderate risk of bias found that the odds of hospitalisation increased for every year of age [ 29 , 44 ] and decade of age [ 28 , 47 ]. On the contrary, one cohort study with moderate risk of bias set in workplaces found workers between 30–39 years of age were at greater risk of hospitalisation due to LBP compared to older workers (RR 1.87, 95% CI 1.3–1.86) [ 53 ]; and a further two studies set in workplaces found the risk of hospitalisation for sciatica decreased with age (HR 0.59, 95% CI 0.38–0.9 women, HR 0.6, 95% CI 0.4–0.91 men) [ 32 ] and (HR 0.23, 95% CI 0.12–0.46) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most guidelines recommend physical therapy and manual therapy in selected patients 14. Patients presenting to the ED may report higher pain levels,51 may be afraid and request quicker resolution of symptoms32 52 as compared with patients presenting to the general practitioner (GP) 49…”
Section: Methodsmentioning
confidence: 99%